Concurrent associations between mothers' references to internal states and children's social understanding in middle childhood. Issue 3 (24th January 2019) - Paine, Amy L.; Hashmi, Salim; Roberts, Siwan; Fyfield, Rhiannon; Hay, Dale F.
Abstract: Although it is well established that features of maternal speech are associated with children's social understanding in the preschool years, few studies explore this relationship in middle childhood. Within the context of a prospective longitudinal study of a representative community sample of families (subsample n = 207, mean age = 82.88 months), we investigated concurrent associations between mothers' internal state language and aspects of 7‐year‐olds' social understanding, including children's understanding of belief and spontaneous references to internal states during free play. When sociodemographic, maternal, and child characteristics were controlled, mothers' references to their own cognitions were associated with dimensions of children's social understanding. Our findings suggest that exposure to others' perspectives contributes to children's advanced understanding of minds, which has implications for interventions that foster social understanding.